Study of P(VDF-TrFE) for Structures via 3D Printing - Caetano, Bernardo Garcia (2020)
This work is focussed on using additive manufacturing (AM) to produce electroactive structures using fused deposition modelling (FDM) and P(VDF-TrFE) as a ferroelectric polymer which will confer electroactive properties to printed structures. The FDM, commonly called 3D printing, was chosen due to its emergence in the industry segment with low-cost production and the capability of projecting prototypes without shape limitations, converting a digital design in a physical object. Beyond these features, the possibility of using functional materials and their properties in the production of sensors and actuators was one of the main reasons for the increased interest in this technology. The boundaries of 3D printing process were explored during the production in order to obtain a uniform and homogenous thin film. It was used a P(VDF-TrFE) filament that was previously extruded to make possible the use of additive manufacturing process. Subsequently, a commercial conductive PLA filament was used to produce electrodes for the electrical characterization of the electroactive films. P(VDF-TrFE) films with 65 μm and aluminium electrodes yielded the best results with a pyroelectric coefficient of 3 μC m-2 K-1. The aforementioned sample was used to produce a fully 3D printable pyroelectric sensor. This sensor was made of P(VDF-TrFE), commercial conductive PLA and conventional PLA. The P(VDF-TrFE) provides electroactive properties, conductive PLA enables the creation of conductive tracks and the conventional PLA gave structural basis to the device.